Flow Forming Process for Annealed AISI 5140 Alloy Steel Tubes - YALÇINKAYA, SENAİ (Springer Science and Business Media Deutschland GmbH, 2021)
Flow forming process performed on annealed AISI 5140 steel material which called “preform” by 50% reduction ratio in this experimental study. The mechanical properties such as tensile strength, yield strength and hardness and microstructures were investigated in order to see the effect of flow forming process on the tested materials. The changes of these properties were evaluated in terms of microstructural observation and hardness tensile measurement. The hardness distribution and microstructural characterization were investigated throughout the wall thickness of the workpiece. The experimental results indicated that the hardness differences occurred because of the roller force effect on the outer surface was more than the force on the inner surface of the workpiece and faster coolant rate. In addition, severely grain orientations were observed, hardness, yield and tensile strength of the workpiece enhanced significantly because of dislocation generation and pile-up during plastic deformation. Although the yield and tensile strength increased, elongation properties reduced after the flow forming operation. Besides, the homogeneous grains orientations were observed throughout the wall thickness of the workpiece due to application the flow forming. © 2021, Springer Nature Singapore Pte Ltd.
Keywords: 5140 steel; CNC flow forming machine; Cold working; Flow forming; Hardness distribution; Microstructure; Reduction ratio; Tensile test